2022
DOI: 10.3390/sym14102089
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model with Independent Control of Load–Displacement Curve Branches for Brittle Material Strength Prediction Using Pre-Peak Test Loads

Abstract: The relevance of problems related to the fracturing of engineering materials and structures will not decrease over time. Fracture mechanics methods continue to be developed, which, combined with numerical methods of computer modeling, are implemented in software packages. However, this is only one facet of the complex of actual problems related to modeling and analyzing the behavior of brittle materials. No less important are the problems of developing not only numerical, but also new analytical models. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Thus, model (14) and a modification of this model (17) represent two new steps in the progress of models of this class. The universality of models (14)–(17) is explained by the possibility of using them to independently control the pre-peak and post-peak branches of the full load–displacement (stress–strain) curve [ 6 , 32 ]. The parameters and specified in (17) can be integers and fractions.…”
Section: Conceptual Aspects Methodology and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, model (14) and a modification of this model (17) represent two new steps in the progress of models of this class. The universality of models (14)–(17) is explained by the possibility of using them to independently control the pre-peak and post-peak branches of the full load–displacement (stress–strain) curve [ 6 , 32 ]. The parameters and specified in (17) can be integers and fractions.…”
Section: Conceptual Aspects Methodology and Resultsmentioning
confidence: 99%
“…Note that according to [ 33 ], the values of the post-peak modulus significantly depend on the stiffness of the test machine and, for example, during uniaxial compression of marble, these values can vary in the range from −550 to −0.49 GPa. To improve the accuracy of modeling the post-peak stage of axial deformation, it is reasonable to use independent control of the parameters of the pre-peak and post-peak branches of the full stress–strain curve [ 32 ]; details of this issue are beyond the scope of this paper.…”
Section: Conceptual Aspects Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper uses the Blagojevich analytical model [34], which belongs to the class of simple but sufficiently versatile load-displacement models, a review of which can be found in [35]. The application of modifications of this model to the analysis of frozen soils and some rocks is considered in [36,37]. However, when applying this model to the analysis of wood, it is necessary to take into account features that have not been previously considered in sufficient detail in the known literature.…”
Section: Load-displacement Curve In Compression Tests Of Wood Along T...mentioning
confidence: 99%
“…In this paper, we use the Blagojevich analytical model [34], which belongs to the class of simple but rather universal load-displacement models, a review of which can be found in [35]. Using [36,37], we write the basic equation of the model in terms of load-displacement (𝐹-𝑢):…”
Section: Load-displacement Modelmentioning
confidence: 99%